PRODUCTION OF Nonomuraea sp. ID 06-A0189 INULIN FRUCTOTRANSFERASE AND PREPARATION OF DFA III FROM INULIN USING THE ENZYME - Pudjiraharti, Sri (Teknologi Indonesia, 2016)
Inulin Fructotransferase (IFTase) converts inulin into difructose anhydride III (DFA III), a functional oligosaccharide. The aim of this study is to find out optimum aeration rate for IFTase production by Nonomuraea sp. ID06-A0189 in 1.5 L fermenter scale. Fermentation was conducted at 30 o C, pH 7.0, 150 rpm and different aeration rates (0.5, 0.75, and 1.0 vvm) for four days. The results showed the higher the aeration rate used, the higher the enzyme activity produced. The highest activity of 9.3 U/mL was produced at 1.0 vvm after 4 days. To find out the ability of inulin fructotransferase to convert inulin into DFA III, the crude enzyme was applied in 50 mL reaction mixture containing 50 and 100 g/L inulin, pH 5.5, 65 o C, for 12 hours. DFA III concentration was measured by high performance liquid chromatography (HPLC). The result indicated the highest DFA III concentration of 56.7 g/L was resulted after twelve hours with the conversion yield of inulin into DFA III was around 57%